The Reconstruction of Gender-Responsive Labour Law Enforcement: Repositioning the Department of Manpower in Addressing Sexual Violence Against Women in the Indonesian Workplace - Chifa Azyana Adly meknesya; Nikmatul Husna; Muhammad Firmansyah; Meldyana Permata Abdillah; Ari Affandi Sagala (ISNU Sumatera Utara, 2026)
Sexual violence against women in the workplace remains a persistent structural challenge that undermines workers' dignity, equality, and the realization of decent work. Although Indonesia has strengthened its legal framework through Law Number 12 of 2022 on Sexual Violence Crimes, Minister of Manpower Decree Number 88 of 2023, and related labour regulations, enforcement remains fragmented and largely reactive. This study examines the role of the Department of Manpower in enforcing labour laws related to workplace sexual violence, identifies weaknesses within the current enforcement system, and proposes a gender-responsive enforcement model to enhance victim protection. The research employs a normative juridical method using statutory, conceptual, comparative, and case approaches, supported by international labour standards and human rights instruments, including ILO Convention No. 190 and CEDAW. Primary legal materials consist of Indonesian legislation and international instruments, while secondary materials include scholarly literature, judicial decisions, government reports, and international publications. The findings indicate that workplace sexual violence constitutes not only an individual criminal offence but also a structural labour law violation arising from failures in workplace governance, employer accountability, and state supervision. The study further reveals that the Department of Manpower's effectiveness is constrained by fragmented institutional authority, limited labour inspection capacity, weak inter-agency coordination, and the absence of integrated victim-centred enforcement mechanisms. Accordingly, this research proposes a Gender-Responsive Labour Law Enforcement Model (GRLEM) integrating preventive supervision, gender-sensitive labour inspection, institutional coordination, victim protection, and effective administrative sanctions. The model contributes to labour law scholarship by transforming labour inspection into a human rights-based enforcement mechanism that supports safe, equitable, and violence-free workplaces in Indonesia.